CCAFS East Africa Regional Science Workshop Report - Ouma, R.; Musoke MN; Radeny, Maren A.O.; Kabugi A (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The East Africa regional program of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) hosted a three-day workshop to engage with partners from agricultural research, agricultural extension, climate services and products, food security, and early warning systems in East Africa. The overall objective of the workshop was to plan and develop thematic research to support climate risk management, adaptation and mitigation options in East Africa, resulting in four to five project concepts that can be supported as seed participatory action research (PAR) activities. From these seed activities, CCAFS intends to build longer term projects from those with the greatest potential to deliver bigger outcomes and impact. The workshop built on the regional needs for research and priorities identified from previous national and regional workshops in 2011.